2016
DOI: 10.3390/ijms17071029
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins and Brain Tumors

Abstract: Brain primary tumors are among the most diverse and complex human cancers, and they are normally classified on the basis of the cell-type and/or the grade of malignancy (the most malignant being glioblastoma multiforme (GBM), grade IV). Glioma cells are able to migrate throughout the brain and to stimulate angiogenesis, by inducing brain capillary endothelial cell proliferation. This in turn causes loss of tight junctions and fragility of the blood–brain barrier, which becomes leaky. As a consequence, the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 147 publications
2
73
0
7
Order By: Relevance
“…In fact, glioma cells have to face the complex architecture of the brain parenchyma, which represents an obstacle to their dissemination. Secretion of metalloproteinases by glioma cells is important to break the extracellular matrix; meanwhile, reducing their volume helps them to sneak into the brain interstitial space and to migrate following a water flux l generated by AQP4 (11). Glioma cell shrinkage able to increase cell migration (48) is similarly triggered by an ion extrusion in turn driving water efflux, as in AVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, glioma cells have to face the complex architecture of the brain parenchyma, which represents an obstacle to their dissemination. Secretion of metalloproteinases by glioma cells is important to break the extracellular matrix; meanwhile, reducing their volume helps them to sneak into the brain interstitial space and to migrate following a water flux l generated by AQP4 (11). Glioma cell shrinkage able to increase cell migration (48) is similarly triggered by an ion extrusion in turn driving water efflux, as in AVD.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of brain fluid homeostasis is a common feature of brain tumors. There is extensive literature on the role of aquaporins in tumor biology, including tumor-associated edema, tumor cell migration, tumor proliferation, and tumor angiogenesis, indicating the need for AQP inhibitors as potentially useful anticancer drugs (10)(11)(12). The role for endothelial aquaporin-1 (AQP1) in the context of tumor angiogenesis is welldescribed (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…[24] According to the current WHO grading system, high grades include grade III and IV lesions. One-year survival rate for high-grade gliomas (HGGs) is 53.7%, while 2-year survival rate for these patients is only 14.6%.…”
Section: Introductionmentioning
confidence: 99%
“…Strong AQP4 expression at the borders between brain parenchyma and major fluid compartments, e.g., between brain ventricles and glia limitans externa or at the BBB, suggests that AQP4 functions in facilitating water flow into and out of the brain and spinal cord. Moreover, an increased AQP4 expression has been demonstrated in glioblastoma multiforme, suggesting it is also involved in malignant brain tumors [27]. Although water transport can occur to a certain extent through simple diffusion across the plasma membrane [28], studies utilizing AQP4 knockouts demonstrated great importance of this water channel in the pathogenesis of brain water imbalance and CNS injuries.…”
Section: Introductionmentioning
confidence: 99%